2020
DOI: 10.1093/mnras/staa2650
|View full text |Cite
|
Sign up to set email alerts
|

Rapid compact jet quenching in the Galactic black hole candidate X-ray binary MAXI J1535−571

Abstract: We present results from six epochs of quasi-simultaneous radio, (sub-)millimetre, infrared, optical, and X-ray observations of the black hole X-ray binary MAXI J1535−571. These observations show that as the source transitioned through the hard-intermediate X-ray state towards the soft intermediate X-ray state, the jet underwent dramatic and rapid changes. We observed the frequency of the jet spectral break, which corresponds to the most compact region in the jet where particle acceleration begins (higher frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 77 publications
1
55
0
Order By: Relevance
“…If the blob is launched when the corona is most compact (MJD ∼58,298) and travels at ∼0.9 c (Bright et al 2020), then a delay of ∼5 days until a radio flare would suggest that the radio-emitting blob is at 10 9 R g . Unfortunately, there have been no published radio measurements of the synchrotron break to independently estimate the radius and distance of the jet ejecta, but this distance is reasonable, when compared to the BHB MAXI J1535-571 where the emission height above the black hole is ∼ 10 8 R g (Russell et al 2020). We also note that recent Chandra imaging showed a transient X-ray jet ejecta at the time of the radio flare, inferring that the ejecta was a cone of 1.5 × 10 4 au by 7.7 × 10 3 au (Espinasse et al 2020).…”
Section: Discussionmentioning
confidence: 94%
“…If the blob is launched when the corona is most compact (MJD ∼58,298) and travels at ∼0.9 c (Bright et al 2020), then a delay of ∼5 days until a radio flare would suggest that the radio-emitting blob is at 10 9 R g . Unfortunately, there have been no published radio measurements of the synchrotron break to independently estimate the radius and distance of the jet ejecta, but this distance is reasonable, when compared to the BHB MAXI J1535-571 where the emission height above the black hole is ∼ 10 8 R g (Russell et al 2020). We also note that recent Chandra imaging showed a transient X-ray jet ejecta at the time of the radio flare, inferring that the ejecta was a cone of 1.5 × 10 4 au by 7.7 × 10 3 au (Espinasse et al 2020).…”
Section: Discussionmentioning
confidence: 94%
“…In the hard state, collimated and continuously replenished compact jets are typically observed in the radio band (Corbel et al 2000;Fender 2001), emitting self-absorbed synchrotron radiation. This results in a flat or slightly inverted radio spectrum (α 0, where the radio flux density follows S ν ∼ ν α ) up to a break frequency ν break located in the infrared (IR) (Markoff, Falcke & Fender 2001;Russell et al 2013bRussell et al , 2014Russell et al , 2020a, after which the jet becomes optically thin. Synchrotron radiation from compact jets can also contribute to the hard X-ray emission (e.g.…”
mentioning
confidence: 99%
“…Contribution from the hot-inflow at these wavelengths seems also be unlikely when considering the preliminary parameters obtained in the previous section. The same authors, instead, conclude that in the near-IR band there may be potential contribution from both jet and accretion disc (Baglio et al 2018;Russell et al 2020). We therefore discuss our results regarding the mid/near-IR connection according to these two possible scenarios:…”
Section: Mid-irmentioning
confidence: 98%
“…Simulations from the internal shocks model have shown that the peak of the near-IR emission region (R) can span, depending on the jet physical conditions, a range of values from ≈ 5 × 10 3 g to ≈ 5 × 10 5 g (Malzac 2014;Malzac et al 2018). Given also the limits to the jet first acceleration zone imposed by Russell et al (2020), we set a conservative value for R of 5 × 10 3 g , which leads to a required jet Lorentz factor of Γ 1.7 and a jet inclination 40 • . It is interesting to notice that this is in good agreement with radio observations of MAXI J1535−571 performed close to our campaign, which revealed a relativistic ejection with a reported inclination ≤ 45…”
Section: Power Spectrum and Qpomentioning
confidence: 99%
See 1 more Smart Citation